A Conversation with Gülden: About (dismantling) securitization, pacification and common sense - Tejeda-Torres, Arturo (Feminist Asylum: A Journal of Critical Interventions, 2023)
Panel Honouring the late Dr. Gülden Özcan, University of Lethbridge, Women Scholars’ Speaker Series